2022
DOI: 10.3390/w14060941
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rainfall Variability and Land Use Change on River Discharge in South Cameroon

Abstract: Climate change, variability and anthropogenic forcings such as land use change are the main forcings of river discharge variability. However, an understanding of their simultaneous impacts on river discharge remains limited in some parts of the world. To shed light on this issue, the objective of this article is to investigate the effects of rainfall variability and land use change on river discharge in the Nyong basin (at Olama and Mbalmayo gauging stations) and some of its sub-basins (So’o and Mefou) over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 56 publications
3
16
0
Order By: Relevance
“…In the Far North region, on the other hand, the increase that began in the 1990s seems to have lasted until the current decade (Table 3). The precipitation evolution in the Adamaoua and North regions in recent decades is similar to that observed in equatorial central Africa [19,20,27]. Contemporary rainfall variations in the Far North region are similar to what has been observed in West Africa and near [15,16,28,29].…”
Section: Interannual Evolution Of Annual and Seasonal Rainfall 311 In...supporting
confidence: 79%
See 2 more Smart Citations
“…In the Far North region, on the other hand, the increase that began in the 1990s seems to have lasted until the current decade (Table 3). The precipitation evolution in the Adamaoua and North regions in recent decades is similar to that observed in equatorial central Africa [19,20,27]. Contemporary rainfall variations in the Far North region are similar to what has been observed in West Africa and near [15,16,28,29].…”
Section: Interannual Evolution Of Annual and Seasonal Rainfall 311 In...supporting
confidence: 79%
“…This is also the case in this study. However, this study reveals a reversal of these trends once known from the 2000s, which has only been demonstrated so far by very few studies [20,30].…”
Section: In the Southern Partmentioning
confidence: 44%
See 1 more Smart Citation
“…The summer dry season flows, for example, recorded the largest drop, yet it was for the autumn rainfall that the largest drop was observed. This could be linked to the fact that in the equatorial region, the precipitation of certain seasons has an impact on the flows of other seasons, most often those which follow them (Liénou et al 2008;Ebodé et al 2022).…”
Section: Impact Of Precipitation On Runoffmentioning
confidence: 99%
“…In other basins such as the Nyong and the Mefou, it has been demonstrated that maximum flows may stay the same or increase, as a result of changes in land use patterns. These changes, which are essentially marked by an increase in impervious areas (buildings, roads and bare soil) to the detriment of the forest, would then compensate for the rainfall deficit by an increase in runoff, hence maximum flows will stay the same in the larger basins and increase in the smaller ones (Ebodé et al 2022). In forested equatorial Central Africa, there are few studies addressing the impact of environmental forcings on flows during future periods using state-of-the-art methodology and new data (Akoko et al 2021).…”
Section: Introductionmentioning
confidence: 99%